Phytoremediation and Potency of Hyperaccumulator Plants - NURIL HIDAYATI (Hayati Journal of Biosciences, 2005)
Phytoremediation is defined as cleaning up of pollutants mediated primarily by plants. It is an emerging technology for environmental remediation that offers a low-cost technique suitable for use against different types of contaminants in a variety of media. Phytoremediation is potentially applicable to a diversity of substances, involving hyperaccumulators heavy metals and radionuclides. It is also applicable to other inorganic contaminants such as arsenic, various salts and nutrients, and a variety of organic contaminants, including explosives, petroleum hydrocarbons and pesticides. At least there are one taxon of plant as hyperaccumulator for Cd, 28 taxa for Co, 37 taxa for Cu, 9 taxa for Mg, 317 taxa for Ni, and 11 taxa for Zn. Extensive progress were done in characterizing physiology of plants which hyperaccumulate or hypertolerate metals. Hypertolerance is fundamental to hyperaccumulator, and high rates of uptake and translocation are observed in hyperaccumulator plants. Hyperaccumulator plants and agronomic technology were undertaken to improve the annual rate of phytoextraction and to allow recycling of soil toxic metals accumulated in plant biomass. These techniques are very likely to support commercial environmental remediation. Most phytoremediation systems are still in development, or in the stage of plant breeding to improve the cultivars for field use. However, application for commercial purposes has already been initiated. Many opportunities have also been identified for research and development to improve the efficiency of phytoremediation